Przedawnienie wszczęcia postępowania dyscyplinarnego wobec studenta obwinionego o popełnienie przestępstwa - Majchrzak, Bartosz (Kwartalnik Prawa Publicznego, 2014)
The present article indicates one of the specific problems of the concurrence of universal criminal responsibility and disciplinary responsibility of students. Above mentioned problem concerns the normalization of limitation of initiating disciplinary proceedings against a student accused of a crime, in particular, the offense of committing plagiarism. An important element of the article is also an attempt to explain the basic notions used in the analyzed legal regulation.